Picture Of The Dark Triad Personality Of Students In Medan City - Febriana, Ruth; Pasaribu, Ronald (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to determine the Dark Triad Personality Description of College Students in Medan City. Based on the results of descriptive analysis of Dark Triad Personality in 350 student respondents in Medan City, several conclusions can be drawn as follows: Overall, the total score of Dark Triad Personality in the study sample was at an average of 56.1 (SD = 8.4), with the majority of respondents included in the medium category. When viewed per dimension, Machiavellianism showed the largest proportion of high categories (77 people; 22.0%), while Narcissism and Psychopathy each had 62 people (17.7%) in the high category. For the three dimensions, the majority of respondents were also in the medium category (Machiavellianism 60.9%; Narcissism 72.6%; Psychopathy 65.4%). The majority picture at the moderate level strengthens the view that the Dark Triad in the non-clinical population is subclinical, that is, present in the form of tendencies that are not always pathological. However, the presence of a high proportion of respondents (especially on Machiavellianism) suggests the existence of a small group that deserves further attention in further studies. The limitations of the study (descriptive design, purposive sampling, and self-report data) should be considered so that the results are best understood as an initial snapshot/sample population, rather than a full generalization to all students in Medan City